2017
DOI: 10.1016/j.rpor.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cyberknife stereotactic radiosurgery and denosumab for giant cell tumour of the skull base: Case report

Abstract: Giant cell tumours (GCT) of the skull is a rare entity with only small number of cases reported in literature and optimal treatment is yet to be determined. These tumours have shown high recurrence rates after incomplete surgery, usually occurring during the first year. Even with new surgical techniques a complete resection in skull base tumours is not always possible without functional compromise. Therefore, adjuvant therapy is essential to enhance local control and quality of life. We report a rare case of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…T h e a p p l i c a t i o n o f S B RT i n G C T B r e m a i n s controversial, with evidence limited to a few case reports (17)(18)(19)(20)(21)(22). The authors of these reports concluded that SBRT offers a radiological regression benefit and improved symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…T h e a p p l i c a t i o n o f S B RT i n G C T B r e m a i n s controversial, with evidence limited to a few case reports (17)(18)(19)(20)(21)(22). The authors of these reports concluded that SBRT offers a radiological regression benefit and improved symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy was the most commonly treatment used (13/25, 52%) as an adjuvant therapy, except in our case where a systemic treatment with denosumab was started following surgery. In addition to radiation, 2 patients (Table 1: cases 12 and 19) were administered intravenous zoledronate (4 mg, once a month) and denosumab, respectively 3,4…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In addition to radiation, 2 patients (Table 1: cases 12 and 19) were administered intravenous zoledronate (4 mg, once a month) and denosumab, respectively. 3,4 Overall, recurrence occurred in 9 cases after their first treatment, with an average time of 5.3 months (range: 2 wk to 24 mo). Most of them (6/9 cases, 67%) only underwent surgery with a partial resection on diagnosis.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations